EFFECT OF GALLIC ACID ON LIPID PROFILE AND ANTIOXIDANT STATUS IN CADMIUM CHLORIDE TREATED RATS - S. Jaffer Ramadhan,; K. Khadim Khudair,; B. Najim Al-Okaily, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to explore the role of gallic acid (GA) in ameliorating in reducing adverse effects of cadmium chloride (CdCl2) on antioxidant status and lipid profile in adult male rats. Twenty-eight (28) adult male rats were divided randomly into four equal groups; they were daily handled for 30 days, as follows: control group (C), received tap water only. (G1), received 100ppm of CdCl2 in drinking tap water, animals in proceeding groups were given in addition to CdCl2 in drinking water the following: intraperitoneal injection of GA 100 mg/kg. daily (G2 group) and the combination of GA and CdCl2 were given to rats in group (G3) in the same pattern.  At the end of the experiment, fasting blood samples were collected and serum was isolated for measuring of antioxidant status and lipid profile. The results showed that administration CdCl2 (G1 group) caused a case of dyslipidemia illustrated by significant elevation in serum cholesterol concentration in lipoprotein low density lipoprotein-cholesterol (LDL-C) and very low-density lipoprotein-cholesterol (VLDL-C), total cholesterol (TC), triglyceride (TAG) and non-HDL-C accompanied with significant decrease in cholesterol of high density lipoprotein (HDL-C) concentrations. The results also revealed a significant elevation in lipid indices including, coronary risk index (CRI), and cardiovascular risk index (CVRI) in CdCl2 exposed rats. While significant elevation in malondialdehyde (MDA) and reduction in (GSH) concentrations observed in the same group comparing to gallic acid and control group, indicating a case of oxidative stress. The current results also recorded that intraperitoneal injection of GA against CdCl2 caused amelioration of all previously estimated parameters.